The economic complexity of the Visegrád countries and the role of trade with Germany - Semanur Soyyiğit; Bartosz Michalski (Central European Economic Journal (CEEJ), 2022)
The contemporary division of production in the global economy poses challenges typical for dependent market economies of the Visegrád countries (V4: Czechia, Hungary, Poland, and Slovakia). This comparative study explores whether the foreign trade of V4 with Germany contributes to their structural change. The analysis seeks to determine the long-term impact of specific intra-industry trade variables on the economic complexity, examined at different levels of technological sophistication. Our findings show that as a result of the characteristics of the trade dynamics, the progress of V4 structural change remains not as comprehensive as expected. As a result, it is critically important to provide incentives aimed at strengthening the geographical diversification of their exports and upgrade their position within the global value chains.
Keywords: F14; F43; O11; O14; O57; 330; economic complexity; international trade; economic transition; structural change; Central Europe; Visegrád countries